STUDI KOMPARASI PENYADAPAN (WIRETAPPING) SEBAGAI ALAT BUKTI ELEKTRONIK MENURUT SISTEM HUKUM DI INDONESIA DAN BELANDA: Comparative Study Of Wiretapping As Electronic Evidence In The Legal Systems Of Indonesia And The Netherlands - Stella Maris Widiana Kalumata; Gandes Candra Kirana (Reformasi Hukum Trisakti, 2025)
The advancement of information technology has led to increased crime, necessitating legal reforms. Wiretapping, while controversial, is an effective tool for uncovering systematic crimes. The problem of this study is examines the regulation, strengths, and weaknesses of wiretapping as electronic evidence in Indonesia and the Netherlands. Employing a normative juridical approach and literature review, the study compares wiretapping mechanisms in both countries. The Findings and the conclusion is reveal that wiretapping is recognized as valid electronic evidence in criminal courts if conducted legally by authorized parties under applicable laws. In Indonesia, wiretapping regulations are fragmented and lack a specific law, resulting in legal uncertainty and overlapping rules. Therefore, Indonesia needs a dedicated wiretapping law that comprehensively regulates its implementation and oversight. Such legislation is crucial to protecting constitutional rights, ensuring legal certainty, and safeguarding individual privacy, allowing judicial processes to operate in an orderly and decisive manner.